Knowledge, attitude, belief and preventive practices of leptospirosis among residents in Hulu Langat rural areas in Selangor, Malaysia - Nozmi, Noramira (2018)
Objective: The aim of this thesis is to identify the level of knowledge, attitude, belief and practices towards leptospirosis. Methodology: A cross-sectional study was conducted among 444 residents aged 18 years old and above. Respondents were sampled using cluster sampling. A set of validated questionnaires were used to determine level of knowledge, attitude, belief and practice. Knowledge consisted of questions on causative agent, diagnosis, modes of transmission, prevention actions, sign, symptoms and complications. Practices consisted of questions on waste management, personal hygiene and environmental cleanliness. Result: This study showed that majority of respondents have poor knowledge (57%), unacceptable attitude (90.3%) and have unacceptable practice (69.1%). Regression analysis was conducted and the result showed that Malay respondents are three times more likely to have good knowledge compared to non-Malay with an odd ratio (AOR)=0.71, 95% confidence interval (CI)=0.209-0.973. Among the KAP variables, attitude (AOR = 4.357, 95% CI = 2.613–7.264) was the only predictor for the preventive practices by logistic regression analysis. Conclusion: Continuous education for rural communities regarding leptospirosis and its prevention should be initiated urgently. Campaigns on leptospirosis using social and mass media should be conducted to alert this multi-ethnic community for better preventive strategies in future.